2014
DOI: 10.1002/jmv.23969
|View full text |Cite
|
Sign up to set email alerts
|

Genome stability of adenovirus types 3 and 7 during a simultaneous outbreak in Greater Manchester, UK

Abstract: A total of 96 isolates of species B adenovirus collected in Greater Manchester, UK and typed previously by serum neutralization were analyzed in five genome regions. Of these, 62 isolates were HAdV-B3 and HAdV-B7 collected during a simultaneous 15 months outbreak. The rest of the isolates were HAdV-B types 3 and 7 and other species B adenovirus types collected in different years following the outbreak. The phylogenetic analysis results of all the isolates in the structural regions hexon L2, penton, and fiber k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The genomic nucleotide identity between the two strains was 99.87%, along with 26 mutations, including 11 synonymous and 10 non-synonymous substitutions, 3 insertions, one deletion and one G to A mutation in L2 NCR ( Table 5 ). Compared with other HAdV types, such as HAdV-B3, -C5, -B7, -B14, -D36, of which the genomes are usually conserved and stable ( Mahadevan et al, 2010 ; Seto et al, 2010b ; Nam et al, 2014 ; Alkhalaf et al, 2015 ; Yu et al, 2016 ; Zhang et al, 2017 ), HAdV-B55 showed similarly conserved genomes when looking at the two strains isolated five years apart (2006 vs 2011). However, the major population distribution of HAdV-B55 associated disease has been changed from juveniles to adults, whereas the disease severity remains similar.…”
Section: Discussionmentioning
confidence: 85%
“…The genomic nucleotide identity between the two strains was 99.87%, along with 26 mutations, including 11 synonymous and 10 non-synonymous substitutions, 3 insertions, one deletion and one G to A mutation in L2 NCR ( Table 5 ). Compared with other HAdV types, such as HAdV-B3, -C5, -B7, -B14, -D36, of which the genomes are usually conserved and stable ( Mahadevan et al, 2010 ; Seto et al, 2010b ; Nam et al, 2014 ; Alkhalaf et al, 2015 ; Yu et al, 2016 ; Zhang et al, 2017 ), HAdV-B55 showed similarly conserved genomes when looking at the two strains isolated five years apart (2006 vs 2011). However, the major population distribution of HAdV-B55 associated disease has been changed from juveniles to adults, whereas the disease severity remains similar.…”
Section: Discussionmentioning
confidence: 85%
“…The hypervariable regions in HAdV-D were found to be sharply reduced in GC nucleotide content relative to the rest of the genome (Robinson et al, 2013a ). Mutations in HAdV are relatively infrequent, with genome stability now documented in some types across decades (Hofmayer et al, 2009 ; Mahadevan et al, 2010 ; Seto et al, 2010 ; Dehghan et al, 2013b ; Robinson et al, 2013a ; Alkhalaf et al, 2015 ). However, those regions of the genome shown to be hypervariable and relatively low in GC content are the very same also shown to undergo homologous recombination (Robinson et al, 2009a , 2011b ; Walsh et al, 2009 ; Zhou et al, 2012 ; Singh et al, 2013 ), driving the evolution of new genotypes.…”
Section: Genomics and Evolutionmentioning
confidence: 99%
“…Among the genotypes of HAdV causing ARD, type 3 (HAdV-3) is the most common one reported to WHO (Echavarría 2009); it is particularly prevalent among children. Outbreaks of HAdV-3 infections are reported globally and recently, including the United States (Lebeck et al 2009), Brazil (Pereira et al 2016), the United Kingdom (Alkhalaf et al 2015), Korea (Lee et al 2010), Australia (Harley et al 2001), Canada (Yeung et al 2009), Singapore (Coleman et al 2019), Malaysia (Li et al 2018), Japan (Fujimoto et al 2008), and China (Zhang et al 2006;Tsou et al 2012;Wo et al 2014;Chen et al 2016;Yu et al 2016;Lu et al 2017;Lin et al 2019;Zhao et al 2019). Despite these widespread and recurring outbreaks, there is no specific drug or vaccine approved for use against HAdV-3 infections.…”
Section: Introductionmentioning
confidence: 99%